Brunei Darussalam’s Economic Transition in a Shifting Global Asia - Khalid, Ahmed M; Jetin, Bruno (Asia in Transition, 2025)
This is an Open Access book. The international political economy is confronted by a number of overlapping crises. These include the climate emergency, rapid technological advancement, the high volume of globalised trade and financial flows, cross-border labour movement, rising inequality, geopolitical tensions, and frequent economic crises and natural disasters. Many developing countries are going through a period of urgent transformation and transition to adopt new policies to cope with such challenges and achieve and maintain sustainable and inclusive socioeconomic development. This path-breaking volume explores the issues shaping the response of Brunei Darussalam, long dependent on its oil and gas sector, to these challenges. The discussions presented here are framed by the notion of ‘development in transition’—a mix of well-designed policies driven by timely implementation, enforcement and monitoring, as well as international cooperation to ensure sustainable development and distribution of benefits on an equitable basis. Through fine-grained analyses of key economic sectors—including natural resources, employment patterns, financial services, global value chains, international trade, tourism and the role of the public sector—the contributors offer a critical assessment of Brunei’s policy responses. This transitional policy mix is situated in relation to the overarching development strategy called Wawasan Brunei 2035 (Brunei Vision 2035), which broadly maps onto the United Nations 2030 Agenda for Sustainable Development Goals. Academic scholars, university students and others interested in the study of contemporary Brunei and broader questions of economic transition in Asia will find this volume an invaluable resource for a deeper understanding of how development paths and priorities are being managed to meet pressing global and local challenges. ; This Open Access edited collection is the first volume dedicated to the economic development of Brunei Darussalam since 1994. It brings together contributions from Bruneian researchers, locally and internationally, to confront current issues related to the economy of Brunei. It traces its journey from an exclusively oil-producing country to a more diversified economy. The work posits that being resource-rich is not always a curse, although it does present numerous obstacles that need to be overcome in order to build a private sector in which new manufacturing and services activities can flourish. The book examines the benefits of trade and regional integration for economic development, and the importance of financial deepening. It shows that the banking sector can play a better role in financial intermediation to finance economic diversification, and emphasises the necessity to create a capital market to mitigate risks. It looks at long-term demographic trends in Brunei, such as the rise of a young and more educated labour force, the access of women to work, and the contribution of migrant workers to growth. It addresses some of the challenges that the economy of Brunei will have to solve. The book does not purport to provide definitive answers, but it unpacks potential solutions. Of interest to researchers focused on Brunei, its society, and economy, this exciting collection is also relevant to scholars studying other resource-rich countries and related social and economic developments.